Investigation on performance and emission characteristics of jack fruit peel biodiesel in VCR using single hole nozzle. (2021) - Mahesh, R.; Muthurajan, K.G.; Surendrababu, K.; Senthilkumar, A.
Abstract: In this experiment, the investigation on performance and emission characteristics of Jack fruit peel biodiesel is done in single cylinder, constant speed, water cooling system Variable Compression Ratio engine using single hole nozzle at various loads. Jack fruit peel Biodiesel is prepared by transesterification process. Analysis is done with three combination of Jack fruit bio-oil with diesel as 20:80, 40:60 and 60:40. From the study it is found that the emission characteristics of Carbon monoxide, Hydrocarbon and Oxygen in biodiesel are less. On the other hand Nitrogen oxide and Carbon dioxide are less for diesel. The specific fuel consumption (SFC) and Break thermal efficiency (BTE) of these blends are high for biodiesel.